Generalized Picone identity for Finsler p-Laplacian and its applications - Dwivedi, G. (Ukrains’kyi Matematychnyi Zhurnal, 2021)
UDC 517.9 We prove a generalized Picone-type identity for Finsler p-Laplacian and use it to establish some qualitative results for some boundary-value problems involving Finsler p-Laplacian.